Process for the preparation of single-atom catalysts with high dispersion of metal active sites

CN117920197BActive Publication Date: 2026-10-20NANJING TECH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311850181.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2026-10-20
Estimated Expiration
2043-12-29

AI Technical Summary

Technical Problem

[0004]本发明的技术方案为:针对目前采用金属盐作为前驱体制备催化剂而容易造成金属活性位聚集的问题,我们设计了一种以金属有机多面体作为前驱体分散于载体表面,通过金属有机多面体的分解,暴露出单个金属原子和载体发生强相互作用力使金属原子牢固的锚定于载体表面的单原子催化剂

Benefits of technology

[0014]本发明的用于以上催化反应的单原子催化剂是一种金属活性位高分散、耐流失的催化剂,由于载体材料具有很好的比表面积,制备的单原子催化剂金属活性位点高度分散。并且,金属有机多面体和载体存在相互作用力,使得金属有机多面体牢固的存在于载体上,经过高温处理后金属活性位和载体的强相互作用使单个金属位点锚定于载体的表面。单活性位点的牢固锚定使得在苯乙炔选择性加氢和苯甲醇选择性氧化等反应中表现出很好的催化活性和稳定性。同时,本发明制备方法简单,环境友好,经济节能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117920197B_ABST
    Figure CN117920197B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a single-atom catalyst with high dispersion of metal sites, and specific steps are as follows: a carrier graphene oxide and a precursor metal organic polyhedron are weighed respectively; the graphene oxide is dissolved in water to prepare a graphene oxide solution, the metal organic polyhedron is added under stirring, uniform stirring is conducted, then freeze-drying is conducted, the obtained sample is heated to 620-650 DEG C in a protective atmosphere, and calcination activation is conducted for 3-5 hours, so that the precursor is converted into a metal site, and a single-atom catalyst is obtained. The single dispersion of the metal site on the carrier material significantly improves the utilization rate of active sites and catalytic activity. Meanwhile, the interaction force between the metal organic polyhedron and the carrier enables the metal organic polyhedron to be firmly dispersed on the carrier surface, in the subsequent heat treatment process, the strong interaction between the metal and the carrier enables the single metal to be anchored on the carrier surface to form the single-atom catalyst, the loss of active sites is reduced, and the service life of the catalyst is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing a highly dispersed and stable single-atom catalyst with metal active sites and the application of the prepared catalyst; in particular, it relates to a method for preparing a single-atom catalyst for selective hydrogenation of phenylacetylene and selective oxidation of benzyl alcohol. Background Technology

[0002] Single-atom catalysts have recently attracted significant attention in the field of catalysis because they involve the dispersion of isolated single metal atoms on a specific solid support. Single-atom catalysts possess advantages such as high atom utilization, ease of separation, good stability, and reusability, thus showing great promise for catalytic applications. Currently, the main methods for preparing single-atom catalysts are the traditional solution method based on co-precipitation, the equal-volume co-impregnation method, and the latest atomic layer deposition method. Furthermore, selecting suitable precursors is helpful for the synthesis of single-atom catalysts. Currently, the main precursors for synthesizing single-atom catalysts are still metal salts, which greatly limits the synthesis methods of single-atom catalysts. Moreover, such precursors are prone to causing metal aggregation, thereby limiting catalytic activity. Therefore, the synthesis methods of single-atom catalysts still need further research and development. Metal-organic polyhedra are usually prepared by the self-assembly of metal ions and functionalized organic ligands (Chem. Soc. Rev., 2021, 50, 528-555). Due to their unique structure and self-assembly properties, they are widely used in catalysis, adsorption, molecular sensing, and other fields. Furthermore, the metal in metal-organic polyhedra is isolated, and the ligands can contain nitrogen, making them suitable as precursors for the preparation of single-atom catalysts. Summary of the Invention

[0003] The purpose of this invention is to provide a method for preparing a single-atom catalyst with highly dispersed metal active sites, thereby overcoming the shortcomings of existing technologies. This single-atom catalyst is prepared by methods such as impregnation, freeze-drying, and activation, and can be used as a catalyst for reactions such as selective hydrogenation of phenylacetylene and selective oxidation of benzyl alcohol, and can catalyze reactions under relatively mild conditions.

[0004] The technical solution of this invention is as follows: Addressing the problem of metal active site aggregation that easily occurs when using metal salts as precursors in catalyst preparation, we designed a single-atom catalyst in which metal-organic polyhedra are dispersed on the support surface as precursors. Through the decomposition of the metal-organic polyhedra, individual metal atoms are exposed, and strong interactions occur between the metal atoms and the support, firmly anchoring the metal atoms to the support surface. Single-atom catalysts can improve the utilization rate of metal active sites and enhance catalytic performance. Furthermore, because the metal is anchored to the support surface in a single-atom state, it is less prone to leaching, thus significantly improving its catalytic stability. Based on this, highly active single-atom catalysts using different types of metal-organic polyhedra as precursors were prepared and applied to catalytic reactions such as the selective hydrogenation of phenylacetylene and the selective oxidation of benzyl alcohol.

[0005] The specific technical solution of this invention is as follows: a method for preparing a single-atom catalyst with highly dispersed metal active sites, the specific steps of which are as follows: weigh the support graphene oxide and the precursor metal-organic polyhedron respectively; dissolve the graphene oxide in an aqueous solution to prepare a graphene oxide solution, add the metal-organic polyhedron under stirring, stir evenly, and then freeze-dry. The resulting sample is heated to 620℃~650℃ and calcined for 3~5h to activate it, so that the precursor is converted into metal sites, thus obtaining the single-atom catalyst.

[0006] Preferably, the concentration of the graphene oxide solution is 5-10 mg / ml; the mass ratio of the metal-organic polyhedron to the carrier material is 0.025-0.05:1.

[0007] Preferably, the metal-organic polyhedron is M2L2, M4L'4 or M6L”4, wherein M is ethylenediamine palladium nitrate, L is 1,2-bis(4-pyridyl)ethane, L' is 4,4-bipyridine, and L” is 2,4,6-tris(4-pyridine)1,3,5-triazine.

[0008] Preferably, the freeze-drying temperature is -85℃ to -65℃; the freeze-drying time is 3 to 5 days.

[0009] Preferably, the heating rate is 2-5°C / min; the protective atmosphere is argon or nitrogen.

[0010] The present invention also provides a single-atom catalyst prepared by the above method.

[0011] This invention also provides the application of the above-mentioned single-atom catalyst in the selective hydrogenation reaction of phenylacetylene, the specific steps of which are as follows: ethanol, phenylacetylene, and the single-atom catalyst are placed in a reaction flask, purged with hydrogen gas (generally 5 times), then connected to a hydrogen balloon, heated to a specific temperature, stirred for a period of time, and then centrifuged to obtain styrene. The molar ratio of ethanol to phenylacetylene is 83–85:1, the mass ratio of phenylacetylene to catalyst is 8–10:1, the reaction temperature is 40–70°C, and the reaction is carried out for 4–6 hours under stirring.

[0012] This invention also provides the application of the above-mentioned single-atom catalyst in the selective oxidation reaction of benzyl alcohol, the specific steps of which are as follows: benzyl alcohol and catalyst are added to a container, purged with oxygen (generally 5 times), and heated to a specific temperature. Then, an oxygen cylinder is connected while stirring, and the reaction is carried out under reflux for a period of time. Finally, the product is obtained by centrifugation, and the product content and ratio are analyzed by gas chromatography. The mass ratio of benzyl alcohol to catalyst is 52-55:1, the reaction temperature is 120-140℃, and the reaction time is 4-6 hours.

[0013] Beneficial effects:

[0014] The single-atom catalyst of this invention for the above-mentioned catalytic reactions is a catalyst with highly dispersed and resistant to leaching of metal active sites. Due to the excellent specific surface area of ​​the support material, the metal active sites of the prepared single-atom catalyst are highly dispersed. Furthermore, the metal-organic polyhedra and the support exhibit interaction forces, ensuring that the metal-organic polyhedra are firmly attached to the support. After high-temperature treatment, the strong interaction between the metal active sites and the support anchors individual metal sites to the surface of the support. This firm anchoring of single active sites results in excellent catalytic activity and stability in reactions such as the selective hydrogenation of phenylacetylene and the selective oxidation of benzyl alcohol. Simultaneously, the preparation method of this invention is simple, environmentally friendly, and economical and energy-saving. Attached Figure Description

[0015] Figure 1 The following are transmission electron microscopy and spherical aberration electron microscopy characterization analysis results of Example 1 of the present invention, wherein Figures a1 and a2 are transmission electron microscopy images of comparative sample A and sample 1-1, respectively, and Figure a3 is a spherical aberration electron microscopy image of sample 1-1.

[0016] Figure 2 The following are transmission electron microscopy and spherical aberration electron microscopy characterization analysis results of Example 2 of the present invention, wherein Figure b1 and b2 are transmission electron microscopy images of comparative sample B and sample 2-1, respectively, and Figure b3 is a spherical aberration electron microscopy image of sample 2-1.

[0017] Figure 3 The following are transmission electron microscopy (TEM) and spherical aberration electron microscopy (SEM) characterization analysis results of Example 3 of the present invention. Figures c1 and c2 are TEM images of comparative sample C and sample 3-1, respectively, and figure c3 is an SEM image of sample 3-1. Detailed Implementation

[0018] To make the above-mentioned objectives, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to specific examples.

[0019] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0020] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0021] Example 1:

[0022] According to Table 1, M2L2 (M: ethylenediamine palladium nitrate, L: 1,2-bis(4-pyridyl)ethane) was synthesized according to the literature (Chem. Eur. J. 2019, 25, 12241-12269). 3.65 mg of M2L2 was weighed and dissolved in 5 mL of deionized water, then added to 13.25 mL of graphene oxide aqueous solution (10 mg / mL). -1 The mixture was stirred for 24 hours. The resulting mixture was then frozen with nitrogen and dried in a freeze dryer for 3 days at -85°C, yielding a black, spongy solid. This material was then placed in a tube furnace and heated at an argon atmosphere at a rate of 2°C / min. -1 The temperature was raised to 640℃ and held for 3 hours to obtain a single-atom catalyst in which palladium is dispersed in graphene.

[0023] Comparative Example: According to Table 1, accurately weigh 2.9 mg of ethylenediamine palladium nitrate and dissolve it in deionized water. Add the resulting solution to 13.25 mL of graphene oxide aqueous solution (10 mg / mL). -1 The mixture was stirred for 24 hours. The resulting mixture was then frozen with nitrogen and dried in a freeze dryer for 3 days at -85°C, yielding a black, spongy solid. This material was then placed in a tube furnace and heated at an argon atmosphere at a rate of 2°C / min. -1 The temperature was raised to 640℃ and held for 3 hours to obtain control sample A.

[0024] Table 1

[0025]

[0026] Transmission electron microscopy was used to characterize the palladium active sites of sample 1-1 and control sample A. The results are as follows: Figure 1 As shown. From Figure 1 As can be seen, compared to sample A, large particles of palladium active sites aggregated, while samples 1-1 did not exhibit this aggregation. Further aberration-corrected electron microscopy characterization of samples 1-1 revealed that palladium was dispersed on the graphene surface as individual metal sites. The key feature is that the metal-organic polyhedron precursor generates single-atom sites through a two-step reduction method during inert atmosphere calcination. First, in the low-temperature stage, the metal-organic polyhedron precursor decomposes into metal nanoparticles; in the high-temperature calcination stage, the metal nanoparticles continue to react with the support, decomposing into isolated metal ions and anchoring them in the vacancy defects of the support, forming a single-atom catalyst.

[0027] Selective hydrogenation of phenylacetylene was tested on control sample A and control sample 1-1. 3.94 g of ethanol, 93 mg of phenylacetylene, and 10 mg of catalyst were weighed and added to a flask. A hydrogen balloon was attached, and the mixture was stirred at 50 °C for 6 h. The supernatant was obtained by centrifugation and analyzed by gas chromatography. The conversion rates of phenylacetylene were 99% and 45%, respectively, while the selectivity for styrene remained at approximately 92% and 96%, respectively. After catalytic regeneration, the conversion rate of phenylacetylene in sample 1-1 remained at approximately 97%, and the selectivity for styrene remained at approximately 92%, while the conversion rate of phenylacetylene in control sample A remained at 33%. This indicates that the single-atom palladium catalyst in sample 1-1 has high regeneration performance.

[0028] According to Table 2, the selective oxidation reaction of benzyl alcohol was further tested on control sample A and sample 1-1. First, 5.2 g of benzyl alcohol was added to a flask, followed by 100 mg of catalyst. The mixture was heated to the reaction temperature of 120 °C, and then connected to an oxygen cylinder with stirring. Small amounts of the reaction mixture were collected periodically, centrifuged, and the catalytic reaction results were analyzed qualitatively and quantitatively using gas chromatography. Control sample C showed a benzyl alcohol conversion rate of 21% within 4 hours, with a product selectivity of only 75%, while sample 1-1 achieved a benzyl alcohol conversion rate of 94% within 4 hours, with a product selectivity of 95%.

[0029] Table 2

[0030]

[0031] Example 2:

[0032] According to Table 3, M4L'4 (M: ethylenediamine palladium nitrate, L': 4,4-bipyridine) was synthesized based on the literature (Chem. Eur. J. 2019, 25, 12241-12269). 3.4 mg of M4L'4 was accurately weighed and dissolved in 5 mL of deionized water. This solution was then added to 26.5 mL of an aqueous solution of graphene oxide (5 mg / mL). -1 The mixture was stirred for 24 hours. The resulting mixture was then frozen with nitrogen and dried in a freeze dryer for 4 days at a temperature of -75°C, yielding a black, spongy solid. This material was then placed in a tube furnace and heated at a rate of 4°C / min under a nitrogen atmosphere. -1 The temperature was raised to 630℃ and held for 4 hours to obtain a single-atom catalyst in which palladium is dispersed in graphene.

[0033] Comparative Example: According to Table 3, accurately weigh 2.9 mg of ethylenediamine palladium nitrate and dissolve it in deionized water. Add the resulting solution to 26.5 mL of graphene oxide aqueous solution (5 mg / mL). -1Continue stirring for 24 hours. Freeze the resulting mixture with nitrogen and then freeze it in a freeze dryer for 4 days at -75°C, obtaining a black, sponge-like solid. Place the obtained material in a tube furnace and heat it at a rate of 4°C / min in a nitrogen atmosphere. -1 The temperature was raised to 630℃ and maintained for 4 hours to obtain control sample B.

[0034] Table 3

[0035]

[0036] Transmission electron microscopy was used to characterize the palladium active sites of sample 2-1 and control sample B. The results are as follows: Figure 2 As shown. From Figure 2 As can be seen, sample B showed aggregation of metal particles, while samples 2-1 did not show large particle aggregation. Further aberration-corrected electron microscopy revealed that palladium was dispersed as individual bright spots on the graphene surface. The key feature is that the metal-organic polyhedron precursor generates single-atom sites through a two-step reduction method during inert atmosphere calcination. First, in the low-temperature stage, the metal-organic polyhedron precursor decomposes into metal nanoparticles; in the high-temperature calcination stage, the metal nanoparticles continue to react with the support, decomposing into isolated metal ions and anchoring them in the vacancy defects of the support, forming a single-atom catalyst.

[0037] Selective hydrogenation of phenylacetylene was tested on control sample B and control sample 2-1. 4g of ethanol, 90mg of phenylacetylene, and 10mg of catalyst were added to a flask, a hydrogen balloon was attached, and the mixture was stirred at 40℃ for 4 hours. The supernatant was obtained by centrifugation and analyzed by gas chromatography. The conversion rates of phenylacetylene were 98% and 45%, respectively, while the selectivity for styrene remained at approximately 93% and 97%, respectively. After catalytic regeneration, the conversion rate of phenylacetylene in sample 1-1 remained at approximately 97%, and the selectivity for styrene remained at approximately 92%, while the conversion rate of phenylacetylene in control sample A remained at 43%. This indicates that the single-atom palladium catalyst in sample 1-1 has high regeneration performance.

[0038] According to Table 4, the selective oxidation reaction of benzyl alcohol was further tested on control sample B and sample 2-1. First, 5.3 g of benzyl alcohol was added to a flask, followed by 100 mg of catalyst. The mixture was heated to the reaction temperature of 130 °C, and then connected to an oxygen cylinder with stirring. Small amounts of the reaction mixture were collected periodically, centrifuged, and the catalytic reaction results were analyzed qualitatively and quantitatively using gas chromatography. Control sample C showed a benzyl alcohol conversion rate of 31% within 5 hours, with a product selectivity of only 78%, while sample 2-1 achieved a benzyl alcohol conversion rate of 71% within 5 hours, with a product selectivity of 93%.

[0039] Table 4

[0040]

[0041] Example 3:

[0042] According to Table 5, M6L”4 (M: ethylenediamine palladium nitrate, L”: 2,4,6-tris(4-pyridine)1,3,5-triazine) was synthesized according to the literature (J. Am. Chem. Soc. 2002, 124(45), 13576-13582). 7.5 mg of M6L”4 was accurately weighed and dissolved in 5 mL of deionized water. This solution was then added to 16 mL of an aqueous solution of graphene oxide (10 mg·mL⁻¹). -1 The mixture was stirred for 24 hours. The resulting mixture was then frozen under nitrogen and dried in a freeze dryer for 5 days at -65°C, yielding a black, spongy solid. This material was then placed in a tube furnace under a nitrogen atmosphere and heated at a rate of 5°C / min. -1 The temperature was raised to 650℃ and held for 5 hours to obtain a single-atom catalyst in which palladium is dispersed in graphene.

[0043] Comparative Example: According to Table 5, accurately weigh 4.38 mg of ethylenediamine palladium nitrate and dissolve it in deionized water. Add the resulting solution to 16 mL of graphene oxide aqueous solution (10 mg / mL). -1 The mixture was stirred for 24 hours. The resulting mixture was then frozen under nitrogen and dried in a freeze dryer for 5 days at -65°C, yielding a black, spongy solid. This material was then placed in a tube furnace under a nitrogen atmosphere and heated at a rate of 5°C / min. -1 The temperature was raised to 620℃ and maintained for 5 hours to obtain control sample C.

[0044] Table 5

[0045]

[0046] Transmission electron microscopy was used to characterize the palladium active sites of sample 3-1 and control sample C. The results are as follows: Figure 3 As shown. From Figure 3 As can be seen, sample C showed aggregation of metal particles, while samples 3-1 did not show large particle aggregation. Further aberration-corrected electron microscopy revealed that palladium was dispersed as individual bright spots on the graphene surface. The key feature is that the metal-organic polyhedron precursor generates single-atom sites through a two-step reduction method during inert atmosphere calcination. First, in the low-temperature stage, the metal-organic polyhedron precursor decomposes into metal nanoparticles; in the high-temperature calcination stage, the metal nanoparticles continue to react with the support, decomposing into isolated metal ions and anchoring them in the vacancy defects of the support, forming a single-atom catalyst.

[0047] Further selective hydrogenation tests were conducted on control sample C and sample 3-1. 3.94 g of ethanol, 93 mg of phenylacetylene, and 10 mg of catalyst were added to a flask, a hydrogen balloon was attached, and the mixture was stirred at 70 °C for 5 h. The supernatant was obtained by centrifugation and analyzed by gas chromatography. The conversion rates of phenylacetylene were 99% and 56%, respectively, while the selectivity for styrene remained at approximately 94% and 93%, respectively. After catalytic regeneration, the conversion rate of phenylacetylene in sample 1-1 remained at approximately 99%, and the selectivity for styrene remained at approximately 93%, while the conversion rate of phenylacetylene in control sample A remained at 52%. This indicates that the single-atom palladium catalyst in sample 3-1 has high regeneration performance.

[0048] According to Table 6, the selective oxidation reaction of benzyl alcohol was further tested on control sample C and sample 3-1. First, 5.2 g of benzyl alcohol was added to a flask, followed by 95 mg of catalyst. The mixture was heated to the reaction temperature of 140 °C, and then connected to an oxygen cylinder with stirring. Small amounts of the reaction mixture were collected periodically, centrifuged, and the catalytic reaction results were analyzed qualitatively and quantitatively using gas chromatography. Control sample C showed a benzyl alcohol conversion rate of 23% within 6 hours, with a product selectivity of only 77%, while sample 3-1 achieved a benzyl alcohol conversion rate of 62% within 6 hours, with a product selectivity of 90%.

[0049] Table 6

[0050]

Claims

1. A method for preparing a single-atom catalyst with highly dispersed metal active sites, comprising the following steps: weighing the support graphene oxide and the precursor metal-organic polyhedron; dissolving the graphene oxide in water to prepare a graphene oxide solution, adding the metal-organic polyhedron under stirring, stirring until homogeneous, and then freeze-drying; calcining the resulting sample at 620 ℃~650 ℃ in a protective atmosphere for 3~5 h to convert the precursor into metal sites, thereby obtaining the single-atom catalyst; wherein the metal-organic polyhedron is M2L2 or M4L2. ’ 4 or M6L ’’ 4, where M is ethylenediamine palladium nitrate, L is 1,2-bis(4-pyridyl)ethane, and L... ’ 4,4-Bipyridine, L ’’ It is 2,4,6-tris(4-pyridine)1,3,5-triazine.

2. The preparation method according to claim 1, characterized in that... The concentration of the graphene oxide solution is 5~10 mg / ml; the mass ratio of metal-organic polyhedra to the graphene oxide support is 0.025~0.05:

1.

3. The preparation method according to claim 1, characterized in that... The freeze-drying temperature is -85℃ to -65℃; the freeze-drying time is 3 to 5 days.

4. The preparation method according to claim 1, characterized in that... The heating rate is 2~5℃ / min; the protective atmosphere is argon or nitrogen.

5. A single-atom catalyst prepared by the method described in claim 1.

6. The application of a single-atom catalyst as described in claim 5 in the selective hydrogenation reaction of phenylacetylene.

7. The application according to claim 6, wherein the specific steps are as follows: ethanol, phenylacetylene and a single-atom catalyst are placed in a reaction flask, purged with hydrogen gas and then connected to a hydrogen balloon, and then heated and stirred to react. After the reaction is completed, styrene is obtained by centrifugation; wherein the mass ratio of ethanol to phenylacetylene is 42-45:1, the mass ratio of phenylacetylene to catalyst is 8-10:1, the reaction temperature is 40-70 °C, and the reaction is carried out for 4-6 h under stirring conditions.

8. The application of a single-atom catalyst as described in claim 5 in the selective oxidation reaction of benzyl alcohol.

9. The application according to claim 8, wherein the specific steps are as follows: benzyl alcohol and catalyst are added to a container, purged with oxygen and heated to a specific temperature, then connected to an oxygen cylinder under stirring, reacted under reflux conditions, and finally centrifuged to obtain the product; wherein the mass ratio of benzyl alcohol to catalyst is 52-55:1, the reaction temperature is 120-140℃, and the reaction time is 4-6h.

Citation Information

Patent Citations

  • Atomic-scale dispersed Pd catalyst prepared by using nitric acid vapor method and application thereof

    CN112337462A

  • Preparation method of monatomic catalyst

    CN115739075A

  • Preparation and application of waste paper-based carbon-loaded monatomic noble metal catalyst

    CN116212857A